The language laboratory and the EFL course = El laboratorio de idiomas y la clase de inglés como lengua extranjera - Navas Brenes, César Alberto 1976-
This article examines the role of the audio-language laboratory in language teaching. The writer explains that the language laboratory is still a very helpful tool because learners can reinforce certain areas in which they are experiencing some difficulty such as the internalization of correct grammatical structures, pronunciation, and listening comprehension. This article contains a brief analysis of the results of a survey questionnaire that was given to students of the Conversational English Courses belonging to the Extension Program at the University of Costa Rica. Based on these results, the writer explains that the language laboratory is an essential component in this type of EFL program.